2022
DOI: 10.1515/biol-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals on bacterial community surrounding Bijiashan mining area located in northwest China

Abstract: Heavy metal (HM) pollution is a severe and common environmental problem in mining area soil. It is imperative to understand the micro ecological characteristics of mining area soil for HM contaminated soil remediation. This study described the effects of HM pollution level and soil physical and chemical parameters on microbial diversity. In this study, high-throughput sequencing technology was used to study the effects of HM pollution on the diversity and composition of the soil microbial community. The soil g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…TN and TP are major nutrient sources for bacteria in sediments. When sediments contain significant amounts of heavy metals or polluted by heavy metals, heavy-metal-tolerant bacteria would result in nutrients mobilization (Liu et al, 2022). Thus, both nutrients and heavy metals would also affect the composition of bacterial diversities and communities (Liu et al, 2022).…”
Section: Variations In Sediment Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…TN and TP are major nutrient sources for bacteria in sediments. When sediments contain significant amounts of heavy metals or polluted by heavy metals, heavy-metal-tolerant bacteria would result in nutrients mobilization (Liu et al, 2022). Thus, both nutrients and heavy metals would also affect the composition of bacterial diversities and communities (Liu et al, 2022).…”
Section: Variations In Sediment Qualitymentioning
confidence: 99%
“…When sediments contain significant amounts of heavy metals or polluted by heavy metals, heavy-metal-tolerant bacteria would result in nutrients mobilization (Liu et al, 2022). Thus, both nutrients and heavy metals would also affect the composition of bacterial diversities and communities (Liu et al, 2022). High concentrations of TN and TP were found in Salt River sediments, which contributed to the reproduction and metabolism of bacteria.…”
Section: Variations In Sediment Qualitymentioning
confidence: 99%
“…The HMs of Cu, Pb, and Fe presented a strong positive correlation with the phyla Chloroflexi and Firmicutes but were significantly negatively correlated with Proteobacteria . Earlier reports showed that Cd, Pb, and/or Zn were significantly positively correlated with the abundances of Chloroflexi [ 42 ], Firmicutes [ 43 ], and Patescibacteria [ 44 ], but significantly negatively correlated with the abundance of the Proteobacteria in wastewater treatment. Our findings are similar to these results.…”
Section: Resultsmentioning
confidence: 99%
“…A number of bacterial communities with good heavy metal tolerance and bioremediation potential in extreme environments have been discovered and characterized through high-throughput sequencing technology. According to Liu et al, metal-tolerant Proteobacteria and Actinobacteria are predominant at the phylum level in mining area soils [ 167 ]. The study by Ma et al [ 168 ] indicated that acidic coal gangue was relatively rich with SRB, containing six genera: Desulfosporosinus , Desulfovibrio , Desulfotomaculum , Desulfobulbus , Desulfitobacterium , and Desulfurella .…”
Section: Bioremediation Of Contaminated Sites By Native Microorganismsmentioning
confidence: 99%